Genome‐wide association analysis of salinity responsive traits in Medicago truncatula - Kang, Yun; Torres‐Jerez, Ivone; An, Zewei; Greve, Veronica; Huhman, David; Krom, Nicholas; Cui, Yuehua; Udvardi, Michael (Plant, cell and environment, 2019)
Salinity stress is an important cause of crop yield loss in many parts of the world. Here, we performed genome‐wide association studies of salinity‐stress responsive traits in 132 HapMap genotypes of the model legume Medicago truncatula. Plants grown in soil were subjected to a step‐wise increase in NaCl concentration, from 0 through 0.5% and 1.0% to 1.5%, and the following traits were measured: vigor, shoot biomass, shoot water content, leaf chlorophyll content, leaf size, and leaf and root concentrations of proline and major ions (Na+, Cl−, K+, Ca2+, etc.). Genome‐wide association studies were carried out using 2.5 million single nucleotide polymorphisms, and 12 genomic regions associated with at least four traits each were identified. Transcript‐level analysis of the top eight candidate genes in five extreme genotypes revealed association between salinity tolerance and transcript‐level changes for seven of the genes, encoding a vacuolar H+‐ATPase, two transcription factors, two proteins involved in vesicle trafficking, one peroxidase, and a protein of unknown function. Earlier functional studies on putative orthologues of two of the top eight genes (a vacuolar H+‐ATPase and a peroxidase) demonstrated their involvement in plant salinity tolerance. Genome wide association studies (GWAS) of multiple physiological and biochemical traits related to salinity‐stress adaptation in M. truncatula were carried out using 2.5 million SNPs. Correlation analysis among the traits showed that salinity tolerance in the population is negatively correlated to sodium, chloride, and proline concentration in the leaf, while root proline levels were positively associated with salinity‐stress tolerance. GWAS analyses were performed with a mixed linear model, and 12 genomic regions that are associated with multiple traits each were identified; these regions harbor a total of 214 SNPs and 74 genes. These genomic regions were confirmed by a GWAS analysis using PC1 as a virtual trait, generated from principle component analysis of the 12 traits that are tightly correlated. Significant linkage disequilibrium was observed among these SNPs, possibly indicating co‐evolution of salinity tolerance alleles. Examination of gene expression of eight top suspect genes revealed associations between salinity tolerance and transcript level changes under salinity stress. Earlier functional studies on orthologues of two of the top eight genes (a vacuolar H+−ATPase and a peroxidase) confirmed their involvement in plant salinity tolerance in other species. Functional annotation of potential salinity tolerance genes points to the importance of transcriptional regulation, vesicle trafficking, and ROS scavenging under saline conditions.